Exploring Saudi EFL Learners’ Perceptions and Use of AI-Powered English Learning Platforms in the Context of Vision 2030 - Mubarak, Rami (European Scientific Journal, ESJ, 2025)
This study examines how Saudi EFL students perceive and use AI-based learning tools in English based on the technology acceptance model (TAM) and Saudi Vision 2030. A quantitative descriptive approach was employed in the collection of data via a questionnaire completed by 68 Saudi male undergraduate students in the public universities. As the results have shown, the level of awareness of AI tools was very high (83.8%), and the most used platforms were ChatGPT, Duolingo, and Grammarly. Although the level of awareness of AI tools was high, the actual use of the tools was rather low among students. Students displayed fairly favourable attitudes concerning the usefulness of AI and the benefits of engagement, but reported difficulties associated with overdependence, privacy concerns, and a lack of Arabic compatibility. Overall, the results demonstrate a balanced optimism and propose institutional policies, ethical education, and AI literacy to facilitate successful implementation in Saudi higher education.